Using Open Source Software to Build Digital Collections - Ruest, Nick (My University, 2010)
Description: This will be a 40-45 minute talk on the benefits of using open source technology in building digital collections with 15-20 minute demonstration. The rest of the time will be left for questions & discussion.
Benefits:
1) Explain the benefits of Open Source technology over proprietary software.
2) Show the collaborative benefits of using Open Source software with digital collections
Keywords: drupal; digital collections; open source software; Library and Information Science; Library and Information Science